Out on a limb : selected writing, 1989-2021 - Sullivan, Andrew, 1963- (Avid Reader Press, 2021)
The provocative social and political commentator Andrew Sullivan--the youngest ever editor of The New Republic, founding editor of The Daily Dish, hailed as one of the most influential journalists of the last three decades by The New York Times--presents a collection of his most iconic and powerful essays of social and political commentary from The New Republic, The Atlantic, The NYT Magazine, New York magazine, and more.